The effect of face inversion on the detection of emotional faces in visual search - Savage, R.; Lipp, Ottmar (Routledge, 2014)
Past literature has indicated that face inversion either attenuates emotion detection advantages in visual search, implying that detection of emotional expressions requires holistic face processing, or has no effect, implying that expression detection is feature based. Across six experiments that utilised different task designs, ranging from simple (single poser, single set size) to complex (multiple posers, multiple set sizes), and stimuli drawn from different databases, significant emotion detection advantages were found for both upright and inverted faces. Consistent with past research, the nature of the expression detection advantage, anger superiority (Experiments 1, 2 and 6) or happiness superiority (Experiments 3, 4 and 5), differed across stimulus sets. However both patterns were evident for upright and inverted faces. These results indicate that face inversion does not interfere with visual search for emotional expressions, and suggest that expression detection in visual search may rely on feature-based mechanisms.